Handling of Human Trafficking in the Modern Era in Indonesia - Difta Anggraeni Syawal Li Idul Fitri; Salahuddin Salahuddin; Syamsulrizal Syamsulrizal; M. Syaprin Zahidi (Departemen Sosiologi Universitas Gadjah Mada, 2022)
This article aims to analyze, namely by describing and participating in how to handle human traffic in the modern era that is happening today. The research method used in this research is a systematic literature review (SLR), where the articles are analyzed using 161 scientific articles sourced from previous articles. The purpose of this method is to look for a problem on the issue being studied. This study tries to examine a country's efforts to eradicate human trafficking. In this study, how to deal with trafficking cases that occur, because of the rise of developing technology, which has led to increasing cases of human trafficking. In the modern era, what can be done is to form a community or team to search for or monitor human trafficking activities on social media. In addition, the need for awareness of the surrounding environment also raises awareness of human trafficking. With collaborative efforts with NGO institutions such as the International Organization for Migration (IOM) we hope to minimize cases of human trafficking that occur in Indonesia.